2019
DOI: 10.1101/570846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of differentially expressed genes in hepatocellular carcinoma by integrated bioinformatic analysis

Abstract: 31Hepatocellular carcinoma is one of the most common tumors in the world 32 and has a high mortality rate. This study elucidates the mechanism of hepatocellular 33 carcinoma-(HCC) related development. The HCC gene expression profile 34 (GSE54238, GSE84004) was downloaded from Gene Expression Omnibus for 35 comprehensive analysis. A total of 359 genes were identified, of which 195 were 36 upregulated and 164 were downregulated. Analysis of the condensed results showed 37 that "extracellular allotrope" is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Our findings also showed that CDC20 was a potential key biomarker that played an crucial or essential role for the development and progression of HCC. Different existing studies also supported our findings 10,13,14,17,18,20,24,30,32,37,40,41,44,48,50,[55][56][57] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings also showed that CDC20 was a potential key biomarker that played an crucial or essential role for the development and progression of HCC. Different existing studies also supported our findings 10,13,14,17,18,20,24,30,32,37,40,41,44,48,50,[55][56][57] .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, we proposed UBE2C as a key or core predictor for development of HCC, which was supported by various existing studies 10,18,33,36,41,44,58 . Xiong et al 94 suggested UBE2C as a potential biomarker or gene for HCC.…”
Section: Discussionsupporting
confidence: 60%
“…Another hub gene, AURKA, can increase the expression of anti-apoptotic molecules in tumorigenic tissues. This gene encodes auroa kinase A, which affects the spindle, centrosome, and chromosome segregation therefore it controls G2 and mitosis phases in the cell cycle (62). In addition, it was indicated that overexpression of AURKA can cause genomic instability and produce cells with multinuclear, overexpressed in neuroblastoma, liver cancer, and kidney carcinoma (63).…”
Section: Gene Set Enrichment Analysismentioning
confidence: 99%
“…Meng et al identified 11 hub genes as closely connected to pathogenesis and HCC prognosis (CCNB2, CDK1, CCNB1, CDC20, CCNA2, TOP2A, MELK, TPX2, PBK, KIF20A, and AURKA) [ 37 ]. Yan and Liu identified five hub genes CCNA2, PLK1, CDC20, UBE2C, and AURKA of hepatic cancer, which were dramatically elevated in the Cancer Genome Atlas [ 19 ]. Zhang et al screened 293 frequent DEGs, comprising 103 upregulated and 190 downregulated genes.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse factors implicated in liver cancer are cellular tumor antigen p53 (TP53), axin-1 (AXIN1), catenin β-1 (CTNNB1), and telomerase reverse transcriptase (TERT) promoters as well as other primary genes for mutation generation, p53 cell cycle system, WNT/β-catenin, oxidative stress, RAS/RAF/MAPK, and PI3K/AKT/MTOR pathways along with other main primary signaling pathways. Liu et al used highly efficient microarray technology to screen molecular indicators across all human cancerous tumors, especially for liver cancer, by using Gene Expression Omnibus (GEO) datasets and The Cancer Genome Atlas (TCGA) RNA-sequence, and analysed with the help of bioinformatics methods [18][19][20][21][22]. Gene chip technology can also reliably represent the molecular expression profile and detect genetic variants correlated with HCC in liver cancer studies [23,24].…”
Section: Introductionmentioning
confidence: 99%